THE EFFECT OF TRANSFORMATION LEADERSHIP ON CORE COMPETENCY (World Bulletin of Social Sciences, 2022)
The research aims to explore the impact of transformation leadership on the core competency of the Ministry of Industry and Minerals. The research relied on the questionnaire tool in collecting information, which amounted to 114 distributed among leaders and various administrative units, and through the use of statistical programs and related statistical methods, a set of results was reached, the most important of which are Clearly recognizing the importance of transformation leadership through its reflection on building trust, respect, and sacrificing personal interests for the sake of the public good. Core competency, and on the basis of these results, the research came out with a set of recommendations, the most important of which is the need to raise the levels of core capabilities in the Ministry of Industry and Minerals, by employing transformation leadership behaviors, and strengthening them for all administrative levels in the Ministry of Industry and Minerals .